2023
DOI: 10.3389/fphar.2023.1256188
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the research landscape: Mapping frontiers and hot spots in anti-cancer research using bibliometric analysis and research network pharmacology

Qi Han,
Zhongxun Li,
Yang Fu
et al.

Abstract: Introduction: Network pharmacology has emerged as a forefront and hotspot in anti-cancer. Traditional anti-cancer drugs are limited by the paradigm of “one cancer, one target, one drug,” making it difficult to address the challenges of recurrence and drug resistance. However, the main advantage of network pharmacology lies in its approach from the perspective of molecular network relationships, employing a “one arrow, multiple targets” strategy, which provides a novel pathway for developing anti-cancer drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The Web of Science Core Collection (WoSCC) is a comprehensive scholarly treasure trove covering more than 190 subject areas worldwide. The database is widely recognized as an outstanding resource for bibliometric research in a variety of disciplines, providing superior literature retrieval and citation analysis services (Han et al, 2023).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Web of Science Core Collection (WoSCC) is a comprehensive scholarly treasure trove covering more than 190 subject areas worldwide. The database is widely recognized as an outstanding resource for bibliometric research in a variety of disciplines, providing superior literature retrieval and citation analysis services (Han et al, 2023).…”
Section: Data Collectionmentioning
confidence: 99%
“…It also allows us to explore the contributions made by individuals from different institutions and countries. Medical fields have widely used bibliometrics as a research method in recent years (Cheng et al, 2022;Han et al, 2023). This paper is the first study to systematically analyze therapeutic drug resistance in head and neck cancer using bibliometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, network pharmacology can effectively predict drug efficacy, potential side effects, discover new drug applications, and optimize combination therapies, offering novel insights and tools for tackling complex diseases. [15][16][17] In this research, network pharmacology and bioinformatics were combined to determine the primary targets and pathways implicated in the use of QSDP for treating DM-HF. Furthermore, the molecular targets of QSDP specifically for DM-HF treatment were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is a statistical approach that utilizes public literature databases to conduct quantitative and qualitative evaluation on publications of interest, by which the research trends and hotpots within a specific field can be concluded. Recently, bibliometrics has been employed in the investigation of nanomaterials (Bhandari et al, 2022;Zhao et al, 2022;Han et al, 2023). However, there is a dearth of bibliometric analysis regarding the utilization of nanomaterials in the context of OC.…”
mentioning
confidence: 99%